Influence of sintering temperature on densification and microstructure of Zn3Nb2O8 ceramics derived from nanopowders - Phakkhananan Pakawanit (2018)
Zinc niobate, Zn3Nb2O8, dielectric ceramics were fabricated by sintering Zn3Nb2O8 nanopowders derived from a rapid vibro-milling technique at various temperatures. Phase formation, densification, microstructure and dielectric properties of the ceramics were investigated as a function of sintering temperatures (1000-1200°C), using a combination of X-ray diffraction, Archimedes density measurement, scanning electron microscopy and dielectric measurement, respectively. It has been found that single-phase Zn 3Nb2O8 ceramics with maximum density of ∼98% theoretical density can be successfully produced with appropriate firing temperature, without any firing additives. Moreover, it is seen that the dielectric properties are found to enhance with increasing sintering temperature and grain size. © (2011) Trans Tech Publications.